149 Interaction of dietary protein and endophyte- infected Tall Fescue seed in stocker steers on finishing phase performance and carcass traits - Davis, Matthew E (J Anim Sci, 2019)
Fescue toxicosis is a multifaceted disease that negatively impacts cattle. It was hypothesized that exposure to endophyte-infected fescue during the stocker phase affects finishing phase growth and carcass characteristics. Eight-month-old steers were sorted by weight and randomly assigned to receive one of four treatments for 56 days in confinement: endophyte-free seed (0 ug/ kg ergovaline) with either 18% (EF-18; n = 9) or 14% dietary protein (EF-14; n = 9) and endophyte-infected seed (500 ug/kg ergovaline) with 18% (EI-18; n = 9) or 14% dietary protein (EI-14; n = 9). Following fescue exposure calves were backgrounded on novel endophyte fescue pastures for 8 mo. At 18 mo, all steers were vaccinated, implanted, and reentered the feedlot for a 112 d growing phase and 52 d finishing phase. Body weight was recorded every 28 d and carcass data was collected at slaughter. Data were analyzed using the MIXED procedure of SAS for effects of BW, ADG, dressing percentage (DP), HCW, backfat, ribeye area (REA), KPH, USDA Yield grade (YG), and USDA Quality grade (QG). Statistical significance was determined at P > 0.05) HCW, BW, backfat, REA, DP, or QG. TheEI-14 had a greater ADG (1.69 kg/d) during the feedlot growing phase compared to the other treatment groups (1.53, 1.47, 1.55 for EI-18, EF-14, EF-18, respectively; P > 0.05). Steers stockered on 18% dietary protein had greater BW compared to steers previously fed at 14% (501.3±3.8 vs. 489.7±3.8; P = 0.0339). In addition, 18% protein in stocker diet resulted in greater KPH (2.3±0.2 vs. 1.78±0.2; P = 0.0129) and YG (3.4±0.1 vs. 3.0±0.1; P = 0.0168) compared with steers fed 14% dietary protein. Finishing growth and carcass characteristics were not affected by exposure to ergot alkaloids at weaning as much as dietary protein when cattle had a background period prior to feedlot entry